FINITE ELEMENT ANALYSIS AND EXPERIMENTAL RESEARCH ON SPECIAL SEMI-TRAILER FRAME - WU Wei; LI ShouCheng (Jixie qiangdu)
As the main bearing part of the vehicle,most of the load was undertaken by the frame,so its performance directly influence the performance of vehicle. According to the special requirements for equipment of semi-trailers,a calculation model of the frame was established with the finite element method,which static characteristics under bending conditions were analyzed. Use with experimental results of electrical test strain,the correctness of the model and the analysis method is verified and to provide the basis for further improvement and optimization.